Ultrafine RuP2 nanoparticles supported on nitrogen-doped carbon based on coordination effect for efficient hydrogen evolution. (11th February 2021) - Guo, Bao-Yu; Zhang, Xin-Yu; Xie, Jing-Yi; Shan, Yuan-Hang; Fan, Ruo-Yao; Yu, Wen-Li; Li, Meng-Xuan; Liu, Da-Peng; Chai, Yong-Ming; Dong, Bin
Abstract: It is still a challenge to develop the high-efficiency noble metal-based electrocatalyst with good dispersion and durability for hydrogen evolution reaction (HER) in wide pH range. Herein, we have successfully synthesized a nitrogen-doped carbon (NC) coated ultrafine ruthenium phosphides (RuP2 ) nanoparticles catalyst with a facile method. With the help of ethylene diamine tetraacetic acid (EDTA), the uniform RuP2 nanoparticles with ultrafine size of about 3 nm are well dispersed on the surface of the NC. The directed coordination between EDTA and Ru ion may be responsible for the excellent structure. Benefiting from the superior electrical conductivity of NC carrier and the reduced resistance of electrons to the active site, the prepared ultrafine RuP2 @NC demonstrates the obviously enhanced electrocatalytic activity for HER, which results in higher current density and lower overpotentials (99, 98 and 196 mV to reach 10 mA cm −2 in 0.5 M H2 SO4, 1 M KOH and 1 M PBS, respectively). The stability is also very good due to the close integration between ultrafine RuP2 and NC. This work provides a new view to rationally design and synthesize the highly effective, stable and great dispersion of phosphide-based electrocatalysts for HER. Graphical abstract: Image 1 Highlights: Ultrafine RuP2 particles embedded in nitrogen-doped carbon has been obtained. Uniform RuP2 with the size of about 3 nm are well dispersed on the surface of the NC. The coordination between EDTA and Ru may be the key for this structure. RuP2 @NC demonstrates the obviously enhanced electrocatalytic activity for HER.